TWO NEW WILD SPECIES OF AVERRHOA (OXALIDACEAE) FROM INDONESIA - Rugayah, Rugayah; Sunarti, Siti (REINWARDTIA, 2008)
RUGAYAH & SUNARTI, S. 2008. Two new wild species of Averrhoa (Oxalidaceae) from Indonesia. Reinwardtia 12(4): 325 â 331. â Based on living collections cultivated in Bogor Botanical Gardens and several herbarium specimens kept in Herbarium Bogoriense, Averrhoa dolichocarpa Rugayah & Sunarti (from New Guinea) and A. leucopetala Rugayah & Sunarti (from North Sulawesi) are described as new species. They are compared with A. carambola L. and A. bilimbi L. the only other known species so far.